Предмет: Алгебра,
автор: Манго228
Разложите на множители:
(a+b)^2 - (a-b)^2
И ещё одно:
4(x+y)^2 - 4x^2
Заранее спасибо!
Ответы
Автор ответа:
0
(a+b)² - (a-b)²=((a+b)-(a-b))·((a+b)+(a-b))=(a+b-a+b)·(a+b+a-b)=2b·2a=4ab
4(x+y)²- 4x²=(2(x+y))²-(2x)²=(2(x+y)-2x)·(2(x+y)+2x)=(2x+2y-2x)·(2x+2y+2x)=
=2y·(4x+2y)=4y(2x+y)
4(x+y)²- 4x²=(2(x+y))²-(2x)²=(2(x+y)-2x)·(2(x+y)+2x)=(2x+2y-2x)·(2x+2y+2x)=
=2y·(4x+2y)=4y(2x+y)
Автор ответа:
0
Похожие вопросы
Предмет: Русский язык,
автор: Аноним
Предмет: Физика,
автор: xuzaxanova86
Предмет: Математика,
автор: alinazudchik
Предмет: Математика,
автор: yля
Предмет: Математика,
автор: vladanazarova